History of Western civilization : a handbook - McNeill, William Hardy (Chicago : The University of Chicago Press, 1986)
Renowned historian William H. McNeil provides a brilliant narrative chronology of the development of Western civilization, representing its socio-political as well as cultural aspects. This sixth edition includes new material for the twentieth-century period and completely revised bibliographies. An invaluable tool for the study of Western civilization, the Handbook is an essential complement to readings in primary and secondary sources such as those in the nine-volume University of Chicago Readings in Western Civilization.
PART I: Western Civilization in World history -- PART II: Classical Civilization -- PART III: European Civilization.
Includes bibliographical references and index.
Keywords: CIVILIZATION -- HISTORY -- OUTLINES, SYLLABI, ETC